Molecular Evolution of Calcium Signaling and Transport in Plant Adaptation to Abiotic Stress - Tao Tong (MDPI AG, 2021)
Adaptation to unfavorable abiotic stresses is one of the key processes in the evolution of plants. Calcium (Ca2+) signaling is characterized by the spatiotemporal pattern of Ca2+ distribution and the activities of multi-domain proteins in integrating environmental stimuli and cellular responses, which are crucial early events in abiotic stress responses in plants. However, a comprehensive summary and explanation for evolutionary and functional synergies in Ca2+ signaling remains elusive in green plants. We review mechanisms of Ca2+ membrane transporters and intracellular Ca2+ sensors with evolutionary imprinting and structural clues. These may provide molecular and bioinformatics insights for the functional analysis of some non-model species in the evolutionarily important green plant lineages. We summarize the chronological order, spatial location, and characteristics of Ca2+ functional proteins. Furthermore, we highlight the integral functions of calcium-signaling components in various nodes of the Ca2+ signaling pathway through conserved or variant evolutionary processes. These ultimately bridge the Ca2+ cascade reactions into regulatory networks, particularly in the hormonal signaling pathways. In summary, this review provides new perspectives towards a better understanding of the evolution, interaction and integration of Ca2+ signaling components in green plants, which is likely to benefit future research in agriculture, evolutionary biology, ecology and the environment.